Popular music, cultural policy, and the Festival of Pacific Arts - Bendrups, Dan (Perfect Beat, 2014)
Pacific Island societies share many cultural similarities, one of which is the role of music as a vehicle for cultural heritage and expressions of identity throughout the region. This is reflected in the quadrennial Festival of Pacific Arts (FPA), managed by the Secretariat of the Pacific Community (SPC). The SPC’s cultural policies are largely reflected in the FPA, especially through traditional (ancestral) Indigenous music and dance performances. Popular music is not directly mentioned in SPC cultural policy; however, there has been an increasing trend in popular music appearing in the context of the FPA, alongside and sometimes replacing more traditional types of performance. This article will examine this development, investigating some of the formal and informal processes leading to the inclusion of popular music in FPA events. It will centre on the 2008 and 2012 festivals, examining the performances of the Rapanui (Easter Island) delegations on these occasions.